Pengaruh teknik desinfeksi dengan ekstrak daun salam (syzygium polyanthum w.) Terhadap stabilitas dimensi cetakan alginat (Laporan Penelitian) - Mipta Harlinda; James Handojo (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: Alginate is the main impression material in dentistry and often linked to cross infection in dental practice. Disinfection of the alginate impression proven to be the key in controlling bacterial contamination but also impacting the dimensional stability of alginate impression. Bay leaf extract (Syzygium polyanthum w.) contains antibacterial compounds which can be used as disinfectant agent for alginate impression. Purpose: To analyze the dimensional stability of alginate impression after the disinfectant application with bay leaf extract by spraying and immersion techniques. Methode: The sample of this study is alginate impression made from the mold specification ANSI/ADA no. 18. There are 3 groups of samples, respectively 9 samples in each group. Group A serves as control, group B use spraying technique, and group C use immersion technique. Results were measured by digital caliper and statistically analyzed. Result: One Way Anova resulted in p-values < 0.05, which means a significant difference in dimension after bay leaf extract disinfection procedures with spraying and immersion for 10 minutes. Conclusion: Disinfection technique with 25% bay leaf extract for 10 minutes have effect on alginate impression’s dimensional stability. The discrepancy is well below the ANSI/ADA no. 18 standard of < 0.5% dimensional change. There is no significant difference in dimensional stability between different disinfectant technique.